A study of Rumi's style and method in sentence structure in the third book of Masnavi Sharif - soror kan Beigi; Seyyed Mahmoud Seyed Sadeghi; Shamsalhajeyah Ardalani (مطالعات زبانی و بلاغی)
One form of sentence used to convey secondary meanings is the imperative mood. This article focuses on types of sentences involving imperative mood and conveying secondary signification in Rumi’s Masnavi, which he used in his work with his mastery of language and knowledge of conceptual capacities.  The study   The purpose of this study is to investigate the style and structure of imperative sentences in the third book of Masnavi Sharif.   The authors aim to investigate Rumi’s intention in employing imperative sentences and the ensuing secondary meaning with highest frequency. The type of research is basic and descriptive-analytical, and the findings are examined based on content analysis. The statistical population of the research is the third book of Masnavi. The result of the research indicates that Rumi has used all the secondary meaning, and imperative sentences with secondary meaning are not clearly limited to the same cases mentioned in the books of meanings. Also, the most widely used of secondary meaning are guidance, rest, desire, persuasion and encouragement, pain and supplication, and the expression of multiple meanings has been done simultaneously in one sentence by the speaker.